The Use of Learning Journals with Problem Based Learning Models Against Student Metacognitive Abilities - Trisnawati, Ice; Syafii, Wan; Zulfarina, Zulfarina (FKIP-Universitas Riau, 2020)
This study aims to determine the effect of learning journals with Problem Based Learning (PBL) models on the metacognitive abilities of class X students of SMAN on environmental pollution material. This type of research was quasi-experimental research. The study population was all students of class X SMAN as a hypothetical population. The research sample consisted of 72 students consisting of 36 students in class X MIPA 2 as an experimental class and 36 students in class X MIPA 5 as a control class. Data collection used questionnaires and description problems. Validation used in the form of content validation and empirical validation. The analysis technique used the One Way Anova test analysis. Based on the results of data analysis and discussion show that the use of learning journals with problem based learning models has a very significant effect on students metacognitive abilities in biology learning at SMAN 2 Pekanbaru. The magnitude of the value of the analysis of the average score of the metacognitive abilities of the experimental class in the very good category is 125.53 while in the control class in the good category is 107.43. This shows the metacognitive ability of students who follow the use of learning journals with problem based learning models is better than students who follow conventional learning.